2014
DOI: 10.1021/nn405809c
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Based Simple and Versatile Surface Modification of Polymeric Nano Drug Carriers

Abstract: The surface of a polymeric nanoparticle (NP) is often functionalized with cell-interactive ligands and/or additional polymeric layers to control NP interaction with cells and proteins. However, such modification is not always straightforward when the surface is not chemically reactive. For this reason, most NP functionalization processes employ reactive linkers or coupling agents or involve pre-functionalization of the polymer, which are complicated and inefficient. Moreover, pre-functionalized polymers can lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
324
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(337 citation statements)
references
References 52 publications
(108 reference statements)
5
324
0
1
Order By: Relevance
“…The TEM images of DNPs@PDA and DNPs/N@PDA in Figure 2A clearly indicated that the nanoparticles consisted of a lot of small spherical domains. Thus, the as‐prepared nanoparticles were formed through the secondary aggregation of small nanoparticles from DNPs via surface‐deposited PDA 21. The zeta potential was measured to investigate the surface modification and charge changes of the DNPs (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEM images of DNPs@PDA and DNPs/N@PDA in Figure 2A clearly indicated that the nanoparticles consisted of a lot of small spherical domains. Thus, the as‐prepared nanoparticles were formed through the secondary aggregation of small nanoparticles from DNPs via surface‐deposited PDA 21. The zeta potential was measured to investigate the surface modification and charge changes of the DNPs (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that the dopamine could self‐polymerize to form surface‐adherent polydopamine (PDA) films onto a wide range of materials either organic or inorganic by a spontaneous oxidation reaction in an alkaline solution (pH = 8.5) 18, 19, 20, 21. It was widely used as material surface modification since the PDA shells are stable enough to reach the target cells after intravenous injection 22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Scheme 1, Fe 3 O 4 nanoparticles were first coated with a polydopamine layer via the polymerization of dopamine under alkaline conditions, and the immobilization of thermostable lipase QLM was conducted through the Schiff base reaction between amine groups of lipase and polydopamine as described previously [30]. Arpanaei et al once constructed a poly(acrylic acid)-coated Fe 3 O 4 cluster@SiO 2 for lipase immobilization, in which complicated procedures were performed through the covalent attachment via N-(3-dimethyl aminopropyl)-N-ethyl carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) chemistries [21].…”
Section: Characterization Of Immobilized Lipase Qlm On Polydopamine-cmentioning
confidence: 99%
“…The catechol/quinone in polydopamine could facilitate adhesion and deposition on solid surfaces through chelation or hydrogen bonding, which has been used for the coating of polydopamine layers on various colloidal particles [29]. After the coating of a polydopamine layer on solid surfaces, enzyme immobilization or its conjugation with functional ligands possessing nucleophilic groups (e.g., amine and thiol) can be easily achieved through Michael addition and/or Schiff base reactions [30]. Through this method, trypsin, heparin, and albumin have been successfully immobilized on cellulose paper, polyethylene membrane, magnetic nanoparticles, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the in vivo anti-tumor effects study showed that injecting DTX-loaded Gal-pD-TPGS-PLA/NPs reduced the tumor size most significantly on hepatoma-bearing nude mice [18]. Yeo et al functionalized poly(lactic-co-glycolic acid) (PLGA) NPs with folate, Arg-Gly-Asp, and poly(carboxybetaine methacrylate) as surface modifiers, which showed no cytotoxicity [19].…”
Section: Pda Capsules and Nps As Carriers For Drug Deliverymentioning
confidence: 99%